Comments on reactions of oxide derivatives of uranium with hexachloropropene to give UCl4. (14th April 2015) - Patel, Dipti; Wooles, Ashley J.; Hashem, Emtithal; Omorodion, Harrison; Baker, Robert J.; Liddle, Stephen T.
Abstract : The reactions of U3 O8, UO2 (NO3 )2 ·6H2 O, and UO2 Cl2 with hexachloropropene to make UCl4 are described. Abstract : We report that U3 O8, UO2 (NO3 )2 ·6H2 O, and UO2 Cl2 react with hexachloropropene (HCP) to give UCl4 in 60, 100, and 92% yields, respectively, and report a protocol to recycle the HCP. This renders the preparation of UCl4 more accessible and sustainable. 2, 5-Dichlorohexachlorofulvene has been identified as a significant by-product from these reactions.